AI-Powered Decision Support Systems for MSMEs Growth Strategies in Emerging Markets - Sakova, Megha; Rahayu, Agus; Wibowo, Lili Adi; Dirgantari, Puspo Dewi (Universitas Dharma Wacana, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in emerging markets face significant challenges in strategic decision-making due to limited resources and dynamic environments. This study aims to explore the role of AI-Powered Decision Support Systems (AI-DSS) in supporting growth strategies using the dynamic capabilities theory. The study involved 250 food processing business actors who have adopted or considered implementing AI-DSS, with data analysis conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that dynamic capabilities and dynamic environments significantly influence the adoption of AI-DSS, ultimately enhancing business performance. Furthermore, dynamic environments were found to moderate the relationship between dynamic capabilities and AI-DSS adoption, indicating that adaptability to external changes is crucial in maximizing the benefits of AI technology. This research contributes theoretically to the literature on dynamic capabilities and technology while offering practical implications for food processing entrepreneurs and policymakers in emerging markets. The study highlights the importance of developing adaptive capabilities and leveraging AI technology to improve competitiveness amidst ever-changing business dynamics.